Simultaneous and Positively Correlated NET Formation and Autophagy in Besnoitia besnoiti Tachyzoite-Exposed Bovine Polymorphonuclear Neutrophils - Zhou, Ershun; Conejeros, Iván; Velásquez, Zahady D.; Muñoz-Caro, Tamara; Gärtner, Ulrich; Hermosilla, Carlos; Taubert, Anja (Frontiers in Immunology, 2019)
Given that B. besnoiti tachyzoites infect host endothelial cells of vessels in vivo, they become potential targets for professional phagocytes [e. g. polymorphonuclear neutrophils (PMN)] when in search for adequate host cells or in case of host cell lysis. It was recently reported that B. besnoiti-tachyzoites can efficiently be trapped by neutrophil extracellular traps (NETs) released by bovine PMN. So far, the potential role of autophagy in parasite-triggered ET formation is unclear. Thus, we here analyzed autophagosome formation and activation of AMP-activated protein kinase α (AMPKα) in potentially ET-forming innate leukocytes being exposed to B. besnoiti tachyzoites. Blood was collected from healthy adult dairy cows, and bovine PMN were isolated via density gradient centrifugation. Scanning electron microscopy confirmed PMN to undergo NET formation upon contact with B. besnoiti tachyzoites. Nuclear area expansion (NAE) analysis and cell-free and anchored NETs quantification were performed in B. besnoitia-induced NET formation. Interestingly, tachyzoites of B. besnoiti additionally induced LC3B-related autophagosome formation in parallel to NET formation in bovine PMN. Notably, both rapamycin- and wortmannin-treatments failed to influence B. besnoiti-triggered NET formation and autophagosome formation. Also, isolated NETs fail to induce autophagy suggesting independence between both cellular processes. Finally, enhanced phosphorylation of AMP activated kinase α (AMPKα), a key regulator molecule of autophagy, was observed within the first minutes of interaction in tachyzoite-exposed PMN thereby emphasizing that B. besnoiti-triggered NET formation indeed occurs in parallel to autophagy.